Workshop on Paediatric Regional Anaesthesia, 24-25 February 2003, Paediatric Institute HKL (Kuala Lumpur : Paediatric Institute HKL, 2003)
Workshop on Paediatric Regional Anaesthesia that focus on challenges and controversies that faces by the parents and provides some tips to overcome all those challenges
Editor, Assoc. Prof. Dr. Felicia Lim
VCD fornat
Keywords: Pediatric anaesthesia; Anaesthesia in childhood